Digital business strategy training through social media for students of MTs al-Ittifaqiah 2 - Nurul Huda; Rahayu Amalia; Rasmila Rasmila; Megawati Megawati; Fauzan Azhiman (Universitas Muhammadiyah Magelang, 2023)
Seeing the rapid development of the internet, digital marketing occupies a very strategic position as a mainstream marketing medium. One of them is for branding and marketing a product through social media. This activity aims to add insight to MTS Al-Ittifaqiah Indralaya students to become young entrepreneurs who have digital marketing soft skills to support marketing their products online. The results of this training show that 80% of the participants have understood digital marketing and the use of social media.